Animasi 3 Dimensi Proses Mimikri Bunglon - Muhammad Maulana sumantri; Nyoman Yoga Sumadewa (Jurnal SASAK : Desain Visual dan Komunikasi, 2020)
The limitations possessed by the Elementary School no 26 Mataram in the learning process that they only use printed learning media and books without using tools and materials to see the color changes in the chameleon, so that many students and students canot see how is the process of mimicry in the chameleon. The method used in this development is a method of developing multimedia so that there are results (outputs) in the form of 3-dimensional animated videos to display chameleons who are doing mimicry when threatened and catching prey. It is hoped that with this video the process of mimicry occurring in the chameleon can help and facilitate students in understanding the lesson.